Prevalence of eating disorders among competitive rowers - Keczeli, V.; Gubicskóné Kisbenedek, A.; Verzár, Z.; Hulman, A.; Petrov, I.; Ihász, F.; Alföldi, Z. (Sports, 2024)
Internationally, few studies have been written on the prevalence of eating disorders among rowers, and there is no research on the subject in Hungary. This is particularly important in weight-related sports such as rowing. The aim of this study is to assess the prevalence of eating disorders among rowers. A quantitative cross-sectional study was conducted in the summer of 2023. In a non-random convenience sampling, our target population consisted of certified competitive rowers (n = 222). In addition to socio-demographic, performance-related questions, the anonymous, self-completed questionnaire used the validated The Eating Disorder Inventory (EDI). Results were considered significant when p < 0.05. A total of 57 lightweight (25.67%) and 165 openweight (74.33%) rowers participated in the study. On the perfectionism subscale and the interoceptive awareness subscale, rowers competing in the lightweight category scored significantly higher (p = 0.03; p = 0.05). Scores on the EDI subscales, gender and BMI data did not show significant relationships. Overall, rowers in the openweight group scored higher on the bulimia subscale, but no rowers who met all criteria and could be identified as having eating disorders. Rowers who have only competed in national championships and not in international competitions were more likely to reduce stress levels by eating. The study showed that the prevalence of eating disorders among rowers is no higher than in the general population. However, continued assessment, further extensive research and education of rowers is essential in this area, as weight-related sports will always be a risk group for eating disorders.